Sexual Activity of Indigenenous Ram Base on Ear Type - Hastono, Hastono (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2000)
Research was conducted to know of sexual activity of indigeneous ram in experimental station, Animal Research Institute, Ciawi-Bogor. Twelve ram were roundly mated with two ewes for fiveteen minutes. All ram were allocated into two groups base on ear type (long and short). The variable observed were time of climbing, time and sum of ejaculation interval with time of climbing, and mating efficiency. Data analyses were used t test. The result of analyses showed that first time of ejaculation in ram of long ear type (4,92 ± 2,61 m) was longer than short ear type (1 ± 0,68 minute) (P<0,01). Sum of ejaculation in long ear type (1,33 ± 0,81 time) was leaster than short ear type (3 ± 1,09 time) (P<0,05). Ejaculation interval with to follow climbing in long ear type (5,43 ± 3,23 minute) was longer than short ear type (2,29 ± 1,76 minute) (P<0,05). Mating efficiency showed that highly significantly (P<0,01). In ram of short ear type (3,6 time) was more efficient than ram of long ear type (1,38 time). The first time of climbing, sum of climbing, and ejaculation interval were has not significantly (P>0,05). It was concluded that the mating rate in indigeneous ram of short ear type was higher than long ear type. (Animal Production 2(2): 83-91 (2000) Key words : indigeneous ram, sexual activity, mating efficiency.